Identité de genre, endossement stéréotypique et habileté perçue : le cas spécifique de femmes performantes dans une activité sportive considérée masculine - Millan, C.; Moliner, P. (Movement & Sport Sciences - Science & Motricité, 2017)
This study hypothesizes links between performance in sport and exercise [SE], instrumental and expressive gender's dimensions, sex-stereotypes endorsements and perceived ability. Women's performance in cross-sex-typed SE making these dimensions salient, this study compares surveys results from women who performed in this criteria or not. Results support the hypothesis of links between perceived ability, instrumentality and women cross-sex-typed sport performance. This study also suggest a complex and multidimensional perception of their sport by performant women. These results are discussed through a sociocognitive perspective and raise questions about used measurement tools.